Application of National Embroidery in Modern Fashion and Textile Design for Students - Nematova Tursuntosh Alisher qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the application of national embroidery in modern fashion and textile design for students. Incorporating traditional embroidery techniques into design education enhances students’ creativity, artistic skills, and cultural awareness. The study highlights pedagogical approaches for integrating embroidery into fashion and textile projects, emphasizing both aesthetic development and the preservation of cultural heritage. The research indicates that combining traditional embroidery with contemporary design encourages innovation, problem-solving, and professional competencies in students.